2001
DOI: 10.1046/j.1469-0705.2001.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of fetal ovarian hyperstimulation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…It is thought that lack of maturation of the hypothalamo-pituitary-gonadal axis and lack of complete development of negative feedback mechanisms with discontinuation of placental steroids are involved (42,46). It has been proposed that edema observed in the subjects is related with vascular endothelial growth factor released from the theca and granulosa cells (43,47). It has been reported that fetal ovarian hyperstimulation may occur rarely (47).…”
Section: Problems Related With Mini Pubertymentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that lack of maturation of the hypothalamo-pituitary-gonadal axis and lack of complete development of negative feedback mechanisms with discontinuation of placental steroids are involved (42,46). It has been proposed that edema observed in the subjects is related with vascular endothelial growth factor released from the theca and granulosa cells (43,47). It has been reported that fetal ovarian hyperstimulation may occur rarely (47).…”
Section: Problems Related With Mini Pubertymentioning
confidence: 99%
“…It has been proposed that edema observed in the subjects is related with vascular endothelial growth factor released from the theca and granulosa cells (43,47). It has been reported that fetal ovarian hyperstimulation may occur rarely (47). In a fetus with a gestational age of 35 weeks, macrosomy, placental thickenning, polyhydramniosis, large ovaries (right 17.8, left 16.3 mL), 2 ovarian cysts with large septae and abdominal distention were observed and the clinical picture was associated with the increased level of beta-hCG found in the mother.…”
Section: Problems Related With Mini Pubertymentioning
confidence: 99%
“…This finding was first described by Sedin et al [ 27 ] in the context of ovarian hyperstimulation syndrome in preterm girls. It has also been proposed that edema observed in these subjects is related to vascular endothelial growth factor released from the theca and granulosa cells [ 28 , 29 ]. More recently, other authors reported clinical cases of MP characterized by swelling of the external genitalia observed in preterm girls [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breast growth (42,46) and solitary or monthly vaginal bleeding (47, 48) have been described. The ovarian hyperstimulation syndrome has been diagnosed even before birth (49) and its pathogenesis is still not fully understood. HPG axis immaturity with incomplete development of negative feedbacks after the removal of placental steroids could be involved (45,50).…”
Section: Figures 1 2 Summarize Prenatal and Early Postnatal Changes mentioning
confidence: 99%